2016
DOI: 10.1136/jech-2015-206888
|View full text |Cite
|
Sign up to set email alerts
|

Residential segregation, dividing walls and mental health: a population-based record linkage study

Abstract: BackgroundNeighbourhood segregation has been described as a fundamental determinant of physical health, but literature on its effect on mental health is less clear. While most previous research has relied on conceptualised measures of segregation, Northern Ireland is unique as it contains physical manifestations of segregation in the form of segregation barriers (or ‘peacelines’) which can be used to accurately identify residential segregation.MethodsWe used population-wide health record data on over 1.3 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…The NIMDM ranges from 1-10, with lower values indicating higher levels of deprivation. Previous work in NI has indicated that people with lower NIMDM scores have higher levels of mental illness and poorer mental health [40]. Moreover, recent research which looked at nationwide data of PwD between 2000 and 2010 has shown that both males and females with dementia who lived in more deprived areas had higher levels of mortality in comparison to PwD who lived in less deprived areas [41].…”
Section: Discussionmentioning
confidence: 99%
“…The NIMDM ranges from 1-10, with lower values indicating higher levels of deprivation. Previous work in NI has indicated that people with lower NIMDM scores have higher levels of mental illness and poorer mental health [40]. Moreover, recent research which looked at nationwide data of PwD between 2000 and 2010 has shown that both males and females with dementia who lived in more deprived areas had higher levels of mortality in comparison to PwD who lived in less deprived areas [41].…”
Section: Discussionmentioning
confidence: 99%
“…Work by Maguire et al (2016) reflects a growing awareness in recent years of how important the spatial interface between different groups can be. It is not only the overall degree of spatial separation that matters but also the nature of transitions between residential communities.…”
Section: Limitations and Avenues For Further Researchmentioning
confidence: 99%
“…This method has been validated in previous studies. 43,44 Owing to small numbers in each of the consanguinity categories, measures of area deprivation and area rurality were added to the multilevel models separately to ensure convergence. Third, as per the method above, multilevel multivariable regression models were constructed to estimate the likelihood of psychotropic medication use given the degree of parental consanguinity.…”
Section: Analytic Approachmentioning
confidence: 99%